33.4k views
2 votes
Write the pattern rule as an equation (y = ?x + ?)I don't understand how I'm supposed to do this.

Write the pattern rule as an equation (y = ?x + ?)I don't understand how I'm supposed-example-1
User Joofsh
by
4.9k points

1 Answer

2 votes

Answer: y = 2x + 7

The number of squares in figure 1 is 7

The number of squares in figure 2 is 9

The number of squares in figure 3 is 11

So the pattern is 7, 9, 11

y = 2x + 7, for x >= 0

for the first figure x = 0, then y = 2(0) + 7 = 7

for the second figure x = 1, then y = 2(1) + 7 = 9

for the third figure x = 2, then y = 2(2) + 7 = 11

User Guymid
by
4.7k points